Kerjasama Guru PAI Dengan Guru Walikelas Dalam Penanganan Masalah Karakter Disiplin Peserta Didik (Studi Di SDN 1 Sukatani Cilawu Garut) - Salamudin, Ceceng; Altifa, Wita Dwi (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
This research contains the collaboration between PAI teachers and homeroom teachers in handling students' disciplinary character problems at SDN 1 Sukatani Cilawu Garut. Collaboration is something that is done together with the same goal and is mutually beneficial. With cooperation, work will be completed quickly and problems will be resolved immediately, as at SDN 1 Sukatani Cilawu Garut, there is collaboration between PAI teachers and homeroom teachers in dealing with students' disciplinary character problems. Problems with the disciplinary character of students at SDN 1 Sukatani Cilawu Garut, for example, include students not doing the homework given by the teacher, not respecting their friends, coming late to school, leaving early. This, of course, must immediately find a solution. The aim of this research is to describe the form of collaboration between PAI teachers and homeroom teachers in handling students' disciplinary character problems at SDN 1 Sukatani Cilawu Garut. This research uses a descriptive qualitative method, namely research that discusses a clear picture of the state of the problems in the field. Data collection techniques include observation, interviews and documentation studies. The data analysis technique in this research uses data reduction, data visualization, verification and conclusions, data validity and data reliability. Based on the research results, there are three forms of collaboration between PAI teachers and homeroom teachers in handling students' disciplinary character problems at SDN 1 Sukatani Cilawu Garut, namely: 1). Internal meetings, 2).Home Visit (home visit), 3). Invite competent institutions. Problems with the disciplinary character of students at SDN 1 Sukatani Cilawu Garut include: 1). Being late for class, 2). Coming home from school early, 3). Wearing a less neat uniform, 4). There are students who wear sandals, 5). Students do not do class picket assignments, 6). Students who don't do homework 7). Students are lazy about practicing, 8). Students do not perform Duha prayers, 9). Students fighting. KeywordS: Cooperation, disciplined character, students